Mobile Health applications - untapped potential - Koraćević, Maja; Jovanović, Aleksandar; Pavlović, Dragana; Catić-Đorđević, Aleksandra (Archives of Pharmacy, 2022)
Today, there are a number of applications that allow you to monitor physical activity and health parameters or schedule a medical examination, and can also help you recognize a health problem and react in time. The aim of the present study was to assess the usage of health applications (HApps, health-related mobile and/or web applications) among citizens in Serbia. The anonymous online questionnaire was distributed via social media in the spring of 2020. Data were processed using the IBM SPSS. 506 respondents participated in the research, of which 155 were from the health profession. The majority of respondents were female (73.9%), and the average age was 36.88 ± 11.22. About half of the respondents (48.2%) have a university degree, and 74.9% are employed. Installed HApps on phone/computer have 18.2% of respondents, with a statistically significant difference (p